2015
DOI: 10.4103/0366-6999.151114
|View full text |Cite
|
Sign up to set email alerts
|

G-protein Coupled Receptor 34 Knockdown Impairs the Proliferation and Migration of HGC-27 Gastric Cancer Cells In Vitro

Abstract: Background:Overexpression of G-protein coupled receptor 34 (GPR34) affects the progression and prognosis of human gastric adenocarcinoma, however, the role of GPR34 in gastric cancer development and progression has not been well-determined. The current study aimed to investigate the effect of GPR34 knockdown on the proliferation, migration, and apoptosis of HGC-27 gastric cancer cells and the underlying mechanisms.Methods:The expression of GPR34 in gastric cancer cell line HGC-27 was detected by quantitative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 18 publications
(19 reference statements)
1
18
0
Order By: Relevance
“…In addition, our analyzes revealed targets with less defined roles in placentation with links with placental complications, eg, PLAC4 (", (Tuohey et al, 2013]), and candidates yet to be studied in the context of placental development. For example, BDE-47-induced expression of GPR34 (Figure 5C), which controls aspects of migration in cancer cells (Jin et al, 2015), and may be required for sufficient immune response to pathogens (Liebscher et al, 2011). Our findings, which complement our observations of BDE-47 functional impairment, provide specific pathways with known roles in trophoblast/placental development to be significantly altered with exposure.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, our analyzes revealed targets with less defined roles in placentation with links with placental complications, eg, PLAC4 (", (Tuohey et al, 2013]), and candidates yet to be studied in the context of placental development. For example, BDE-47-induced expression of GPR34 (Figure 5C), which controls aspects of migration in cancer cells (Jin et al, 2015), and may be required for sufficient immune response to pathogens (Liebscher et al, 2011). Our findings, which complement our observations of BDE-47 functional impairment, provide specific pathways with known roles in trophoblast/placental development to be significantly altered with exposure.…”
Section: Discussionsupporting
confidence: 66%
“…For urothelial cancer, WNT7B, SFRP1, DNAJB2, and ATF3 were reported as target genes with cantharidin predicted as a reversal drug [ 62 ]. Some genes captured in this study have been previously identified for an association with cancer to include CNR2 that is associated with bladder cancer cell growth and motility which is linked to the cannabinoid 2 receptor-mediated modifications [ 63 ], GRR34 knockdown was shown to impair proliferation and migration of HGC-27 gastric cancer cells [ 64 ], DDHD2 as a potential cancer marker in human urine [ 65 ], and BACE2 as a prognostic marker in cervical cancer [ 66 ]. The significance of MAPK signaling, integrin-linked kinase, growth inhibitor family member 2, and NRF2-mediated oxidative stress response pathways provides an important linkage of involvement of oxidative stress and DNA damage after arsenic exposure in human which lead to carcinogenesis through dysregulation of these signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells are frequently used as experimental model in basic and clinical studies. MGC803 and HGC27 cell lines have been used for many years in gastric cancer research, however, the difference of their genetic background have not been reported (Tamura et al, 1996;Zhang et al, 2004;Jin et al, 2015). By global transcriptomics profiling for both cell lines, we characterized the differential expression of genes between these two cell lines.…”
Section: Discussionmentioning
confidence: 99%